Plato and the moving image (Value Inquiry Book Series, 2019)
This book shows how and why debates in the philosophy of film can be advanced through the study of the role of images in Plato's dialogues, and, conversely, why Plato studies stands to benefit from a consideration of recent debates in the philosophy of film. Contributions range from a reading of Phaedo as a ghost story to thinking about climate change documentaries through Plato's account of pleonexia . They suggest how philosophical aesthetics can be reoriented by attending anew to Plato's deployment of images, particularly images that move. They also show how Plato's deployment of images is integral to his practice as a literary artist. Contributors are Shai Biderman, David Calhoun, Michael Forest, Jorge Tomas Garcia, Abraham Jacob Greenstine, Paul A. Kottman, Danielle A. Layne, David McNeill, Erik W. Schmidt, Timothy Secret, Adrian Switzer, and Michael Weinman.